O ensino / aprendizagem da metafonia do português como língua estrangeira por aprendizes alemães - Krug, Marcelo Jacó (Contingentia, 2009)
The present article deals with a phenomenon of the portuguese language which is well-known and yet rather neglected in brazilian schools as well as in schools abroad: metaphony. Since this regular vowel change is a phenomenon that foms part exclusively of speech and is not represented in writing, it constitutes a problem for foreign learners, in our case speakers of German. We therefore propose a strategy by the help of which the phenomenon of metaphony in Portuguese can be explained, based on analogies with a similar regular sound change in the German language, called Umlaut. Our study is based upon data collected among students at Christian-Albrechts-Universität in Northern Germany